2020
DOI: 10.1002/ejoc.202000829
|View full text |Cite
|
Sign up to set email alerts
|

Concentration‐Dependent Thermal Isomerization of Nitrile N‐Oxide

Abstract: Kinetically stabilized nitrile N-oxides (NOs) have been regarded as viable tools for the postpolymerization functionalization of common polymers. However, thermal isomerization of NO to isocyanate restricts the applications of NO to industrial use. The reaction mechanism for the thermal isomerization has not been systematically evaluated. Herein, we report the concentration-dependent isomerization of NOs for the first time. The time-course plots suggest that the isomerization of NO [a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…However, the reaction of nitrile N-oxide tends to involve undesirable side reactions with nucleophiles [14] and self-reactions such as dimerization, [16] oligomerization, [17] and isomerization. [18][19][20][21][22][23] Nitrile N-oxide can be kinetically stabilized with neighboring bulky substituents such as an orthosubstituent for aromatic nitrile N-oxide and a quaternary carbon center adjacent to aliphatic nitrile N-oxide. With this concept, we have developed homoditopic stable nitrile N-oxides as a ligation tool, which enables the catalyst-free polymerization of bisdipolarophiles [24,25] and the cross-linking reactions of common polymers.…”
Section: Introductionmentioning
confidence: 99%
“…However, the reaction of nitrile N-oxide tends to involve undesirable side reactions with nucleophiles [14] and self-reactions such as dimerization, [16] oligomerization, [17] and isomerization. [18][19][20][21][22][23] Nitrile N-oxide can be kinetically stabilized with neighboring bulky substituents such as an orthosubstituent for aromatic nitrile N-oxide and a quaternary carbon center adjacent to aliphatic nitrile N-oxide. With this concept, we have developed homoditopic stable nitrile N-oxides as a ligation tool, which enables the catalyst-free polymerization of bisdipolarophiles [24,25] and the cross-linking reactions of common polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Oxazirines [19d,e,k] and acylnitrenes [19d,k] have been suggested as reactive intermediates, as has a dyotropic rearrangement, [19e,h] in which the group R and the oxygen atom migrate simultaneously. For reactions in solution it has been suggested that aggregates or oligomers are involved [19j,n] …”
Section: Introductionmentioning
confidence: 99%